Emotional state of nurses working on the front lines of the COVID-19 pandemic (Research, Society and Development, 2022)
Objective: to describe the perceptions on occupational stress of nurses who worked in Intensive Care Units with patients infected with COVID-19. Materials and Methods: a descriptive-exploratory study, of qualitative approach, with 29 nurses working in five Intensive Care Units in Pernambuco, a Northeastern Brazilian State, public and private reference units for COVID-19. The interviews were conducted between May and September 2020, being audio-recorded and later transcribed. The analysis was done using the condensation of meanings. Results: the presence of the themes stress, fear, insecurity, discouragement, unpreparedness, lack of structure and tiredness were noted, with emphasis on the factors: stress and anguish. Nevertheless, they also demonstrated concern with the family, both because of the isolation and the risk of contamination, besides the fear of social isolation. Final Considerations: results evidenced the need to intensify the offer of psychological treatments aimed at the prevention and promotion of mental health of nurses.